Femtosecond Laser-Matter Interaction: theory, experiments and applications - Gamaly, Eugene (World Scientific, 2011)
This book covers the interaction of laser pulses with solids at nonrelativistic intensity. It connects phenomena from the subtle atomic motion on the nanoscale to the generation of extreme pressure and temperature in the interaction zone confined inside a solid. With mathematics kept to a minimum, this is a highly engaging and readable treatment for students and researchers in science and engineering. The book avoids complex mathematical formulae, and hence, the content is accessible to nontechnical readers. Useful summaries after each chapter provide compressed information for the quick estimates of major parameters in planned or performed experiments. --amazon.com